Pemberdayaan Masyarakat Pesisir melalui Pendidikan Agama Islam dan Peningkatan Literasi: Studi Pelaksanaan KKN di Desa Pekan Tanjung Beringin, Kabupaten Serdang Bedagai - Lufita Sari Sitorus; Siti Nurhaliza; Imel Diana Pardede; Rahmad Mubarok Siregar; Mhd. Hafiz Fadhilah Simanjuntak; M. Alhafiez Ridwan; Ramadhan (STAI UISU Pematangsiantar, 2026)
This article aims to describe, analyze, and evaluate the implementation of the Community Service Learning (KKN) program of Sekolah Tinggi Ilmu Tarbiyah (STIT) Serdang Bedagai for the 2025/2026 Academic Year in Pekan Tanjung Beringin Village, Tanjung Beringin District, Serdang Bedagai Regency, North Sumatra Province. This coastal village is characterized by a predominantly fishing community facing challenges such as low interest in formal education, limited religious understanding among children, and weak literacy and self-confidence among youth. Using a Community Based Research (CBR) approach and descriptive qualitative methods, the study analyzed data obtained through participatory observation, interviews, and activity documentation over 30 days (January 15 – February 14, 2026). The results indicate that an integrative KKN program encompassing Qur'anic tahsin-tahfiz guidance, formal school instruction at MA Al-Washliyah, public speaking and kultum training, Islamic social ethics education, and creative economic empowerment yielded significant positive impacts on participants' religious understanding, literacy, and self-confidence. This article underscores the importance of locally responsive approaches in community service programs, particularly in coastal areas with distinctive socioeconomic characteristics.